Preparing A Strategic Learner By Using Metacognitive Strategies: From Theory Into Practice - Tomo Djudin (Journal of Education and Learning (EduLearn), 2018)
It is unrealistic to expect students to have future literacy about science, information, and technology if their education includes only facts and concepts relevant during the school years. While life presents situations that cannot be solved by learned responses, the metacognitive strategy is brought into play. Metacognitive skills are needed when habitual responses are not successful. Metacognitive skills will enable students to successfully cope with new situations. The main purpose of this paper is to propose a practical model of implementing strategies to increase students’ ability to comprehend texts and find solutions to word problems based on the theories and empirical background of metacognition. In addition, the distinction between metacognition and cognition and explicit instruction on the learning strategies to develop students metacognitive skills were discussed. It concludes that  teachers can raise the level of metacognitive thought in their classrooms by modeling the processes. The use of metacognitive strategies will enable students to be independent and strategic learners.